Segment Coordination Variability During Double Leg Bodyweight Squats at Different Tempos - King, Adam C.; Hannan, Kelci B. (International Journal of Sports Medicine, 2019)
The aims of this study were twofold: 1) to examine lower extremity coordination during bodyweight squats performed at two different tempos, and 2) to establish a reliable measure of segment coordination variability. Eighteen subjects (10 F, 8 M) completed bodyweight squats at preferred (self-paced) and non-preferred (metronome-paced) tempos. A modified vector coding approach used kinematic data to compute absolute couplings patterns and coordination variability for three couplings (foot-shank, shank-thigh, thigh-trunk) in three planes of motion for the descent and ascent phases of a squat cycle. A coordination variability reliability equation was used to determine the number of squats needed for a reliable index of movement variability relative to total variability over 20 squats. Tempo did not significantly alter the absolute coordination patterns of any couplings. The reliability equation revealed that 5–9 squats were needed for a reliable coordination variability measure. Nine squats provided a reliable measure of coordination that is comparable to using 20 double leg squats in the calculation. Using nine squats ensures reliable calculations in the frontal, sagittal and transverse planes at preferred and non-preferred speeds. These results can be used to guide clinical evaluation of acceptable levels of movement variability during rehabilitation.
Keywords: coordination variability; modified vector coding; bodyweight squats